Design and Realization of Wideband Printed Monopole Antenna with Tel-U Logo Patch - Macho Revelino Siahaan; Levy Olivia Nur; Radial Anwar (IJAIT (International Journal of Applied Information Technology), 2020)
One of the challenges of antenna development for wireless communication systems is to create an antenna that can be operated in wide frequency so that a single antenna can be used in various wireless communication technologies. This paper discussed the wideband antenna with Telkom University Logo-shaped patch, using Fr-4 (?r = 4.3) substrate with 1.6 mm thickness. The antenna can be operated in the frequency range of 760 MHz – 13.75 GHz. The gain performance at the working frequency is still above 0 dBi. Hence, the antenna design to work properly for wireless communication systems which require relatively long distances. The Defected Ground Substrate (DGS) method is applied to achieve that bandwidth. Measurement shows the logo-shaped patch antenna achieves 12.994 GHz bandwidth with 1.33 VSWR and gain 2.85 at 921.5 MHz frequency.